Pengaruh Intellectual Capital Terhadap Financial Performance Perusahaan Consumer Non-Cyclicals Listed Di Bursa Efek Indonesia Tahun 2018-2019 - Ignatius Adhimas Garis Nugroho; Munari Munari (Universitas Sains dan Teknologi Komputer, 2021)
The research goals to obtain information and empirical evidence of the influence of intellectual capital on net profit margin, return on invested capital, and return on capital employed. This research was a quantitative research. This research used secondary data which is company financial reports in 2018-2019 taken from Indonesia Stock Exchange. Population of this research was Consumer Non-cyclicals companies listed on Indonesia Stock Exchange 2018-2019. Sample were 43 companies which taken using purposive sampling method based on several criteria. Data analysis was processed using SPSS 23. Data analysis technique used simple linear regression. The results pointed out that intellectual capital had significant positive influence on net profit margin, return on invested capital, and return on capital employed.